Serum Cholesterol, Total Proteins, Phosphorus and Calcium levels in Oestrus and Anoestrus Non Descript Cows - TANDLE, M K; AMANULLH, MOHD; HONNAPPAGOL, S S; KARTIKESH, S M; RAM, JAGJIWAN; SONWANE, S D (The Indian Journal of Animal Reproduction, 2023)
Serum levels of cholesterol, total proteins, phosphorus and calcium were studied in oestrusand anoestrus non descript cows. In oestrus cows, the cholesterol, total proteins and phosphorus levels were significantly higher thananoestrus cows. Higher levels of calcium were recorded in oestrus cows but the difference wasnon significant. Ca:P ratio was higher ( 3: 1) , 1n anoestrus cows than oestrus cows (2.2: 1 ).
Keywords: Serum Cholesterol; Proteins; Phosphorus and Calcium; Cows